Emergency response to out-of-hospital status epilepticus: A 10-year observational cohort study. (25th July 2017) - Semmlack, Saskia; Yeginsoy, Désirée; Spiegel, Rainer; Tisljar, Kai; Rüegg, Stephan; Marsch, Stephan; Sutter, Raoul
Abstract : Objective: To determine the implications of first responses of emergency medical services (EMS) to out-of-hospital status epilepticus (SE) on outcome. Methods: From 2005 to 2014, prehospital and in-hospital data were assessed in consecutive adults admitted to an academic medical center with out-of-hospital SE. Logistic regression was performed to identify variables with a robust association between missed epileptic events by the EMS and no recovery to functional baseline in survivors. Results: Among 213 SE patients, 150 were admitted via EMS. While nonconvulsive SE (NCSE) was missed by the EMS in 63.7%, convulsive SE (CSE) was not missed except in 4 patients with transformation into subtle SE. Missed NCSE was more likely with older age (odds ratio [OR]per year 1.06, 95% confidence interval [CI] 1.02–1.10, p = 0.003) and no seizure history (OR 6.64, 95% CI 2.43–18.1, p < 0.001). The area under the receiver operating characteristic curve for prediction of missed NCSE by these variables was 0.839. Independent predictors for not receiving benzodiazepines were increasing age (ORper year 1.05, 95% CI 1.01–1.08, p = 0.008) and higher Glasgow Coma Scale score (ORper increasing unit 1.21, 95% CI 1.09–1.36, p = 0.001). Missed NCSE was independently associated with increased odds for no return to functional baseline in survivors (OR 3.83, 95% CI 1.22–11.98, p = 0.021). Conclusions: Among patients admitted with out-of-hospital SE, CSE is mostly recognized while NCSE is frequently missed especially in patients with increasing age and no seizure history. This calls for heightened awareness for out-of-hospital NCSE in such patients, as missed NCSE is associated with lack of treatment and less recovery to functional baseline in survivors independent of established outcome predictors.